The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/gox.0000000000002853
|View full text |Cite
|
Sign up to set email alerts
|

Does the Approach of the Lateral Platysmal Bands Widen the Gap between the Medial Bands?

Abstract: Background: The first visible change in an aging face and neck is the loss of neck contour, which can be corrected by treating the platysmal bands; however, it remains unclear as to which is the best strategy to approach these bands. The aim of the present study is to verify whether the lateral platysmal bands approaches, before the medial ones, cause widening of the gap between them. Methods: This is a prospective, randomized, comparative study involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a study conducted by L. Charles-de-Sá et al, the authors aimed to determine whether the traction of the lateral platysma could potentially increase the distance between the medial platysmal bands. However, their findings concluded that the lateral platysmal approach, whether through plication or dissection, does not lead to an expansion of the distance between the medial platysmal bands [31].…”
Section: Mixed Platysmaplastymentioning
confidence: 94%
“…In a study conducted by L. Charles-de-Sá et al, the authors aimed to determine whether the traction of the lateral platysma could potentially increase the distance between the medial platysmal bands. However, their findings concluded that the lateral platysmal approach, whether through plication or dissection, does not lead to an expansion of the distance between the medial platysmal bands [31].…”
Section: Mixed Platysmaplastymentioning
confidence: 94%